Analisis Ergonomi Desain Meja Belajar Mengaji Dan Keluhan Muskuloskeletal Disorders Pada Santri Pondok Pesantren Anwarul Huda Kota Malang Tahun 2019 - Ramadhan, Adnan; Solichin, Solichin; Tama, Tika Dwi; Puspitasari, Sendhi Tristanti (Preventia: The Indonesian Journal of Public Health, 2022)
The position of sitting not ergonomically forced like sitting cross-looking and sitting bent is one of the common causes of musculoskeletal disorders. This research was conducted to describe the ergonomic level design of studying learning tables used by the last step student of Anwarul Huda Islamic boarding school and the perceived complaint by showing which side of the table affects musculoskeletal disorders. The research method is descriptive with cross sectional design against 20 students of Islamic boarding school. The results obtained by the current diniyah table design are made by manufacturers who do not use anthropometric data in determining its size. Also found the most complaints for three consecutive days of data collection with the Nordic Body Map questionnaire which is on the skeletal part of the back, neck and buttocks. It was also found that none of the Islamic boarding school students were in the right sitting position, 30 percent of the sitting position was incorrect, 60 percent of the santri were in the wrong sitting position, and 10 percent of the santri in the sitting position were fatal. This can happen because in an ergonomic analysis using the mix match method the Islamic boarding school table design is all incompatible with the santri anthropometry, the Islamic boarding school table design is not ergonomic has a cause of the appearance of musculoskeletal disorders complaints by student Islamic boarding school.